Global burden of four cardiovascular diseases attributable to low fruits and vegetables intake, 1990–2021, with a forecast to 2044 - He, Xin; Huang, JiaXin; Cao, Hua; Cheng, Zhangbo (Frontiers in Nutrition, 2025)
BackgroundCardiovascular diseases (CVDs) remain the leading global cause of death. The contribution of inadequate fruits and vegetables (F&V) intake to specific CVD subtypes has not been well characterized across places and time.MethodsUsing Global Burden of Disease (GBD) 2021 estimates for 204 countries/territories, we have quantified deaths and disability-adjusted life years (DALYs) from ischaemic heart disease (IHD), hypertensive heart disease (HHD), peripheral artery disease (PAD), and aortic aneurysm (AA) attributable to low fruit or low vegetables intake (1990–2021). We have assessed age-standardized mortality and DALY rates (ASMR, ASDR) and temporal trends via estimated annual percentage change (EAPC), examined patterns by age, sex, and Sociodemographic Index (SDI), decomposed changes into demographics versus epidemiologic effects, and generated forecasts to 2044 using Nordpred.ResultsIn 2021, inadequate F&V intake accounted for a substantial CVD burden worldwide. IHD and HHD dominated deaths and DALYs. Although ASMRs and ASDRs generally declined, absolute deaths rose, driven largely by population aging. AA, PAD, and IHD burdens were higher in men, whereas HHD burden was higher in women. Middle- and low-SDI settings carried greater IHD and HHD burdens, while AA and PAD were more prominent in high-SDI regions. Notably, HHD mortality attributable to low fruits intake increased across all SDI strata. Decomposition analyses indicated aging as the principal driver of rising deaths in high-SDI regions and combined effects of population growth and adverse epidemiologic change in lower-SDI regions. Projections suggested continued increases in deaths with relatively stable ASMRs through 2044.ConclusionDespite improvements in age-standardized rates, persistent dietary risks and demographic aging sustained a high, uneven burden of diet-related CVDs. Equitable, population-level policies to improve F&V affordability and access–particularly in lower-SDI regions–are essential to curb future cardiovascular mortality.